Gambaran Pola Konsumsi Pangan dan Status Gizi Pada Pecandu Narkoba Di Panti Sosial Pamardi Putra Insyaf Sumatera Utara Tahun 2014 - agustia niranda dalimunthe; Etti Sudaryati; Muhammad Arifin Siregar (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2014)
Drug addicts are generally prone to nutritional problems. Nutritional problems experienced by drug addicts due to a decrease in appetite during the period when the influence of drugs and drug withdrawal. Low food intake and takes place in a relatively long period of time will cause a drug addict nutrient deficiency resulted in a decrease in nutritional status. This study aims to determine the pattern of food consumption and nutritional status of drug addicts in Panti Sosial Pamardi Putra Insyaf. This study used a cross sectional design. The study population are drug addicts undergoing rehabilitation in PSPP Insyaf. Samples taken as many as 71 people with purposive sampling technique. Data was collected through interviews using questionnaires, forms of food records, a food frequency form and the form of food history. Drug addicts undergoing rehabilitation in PSPP Insyaf mostly aged 16-19 (57.7%) and undergo the most rehab for 5 months (38%). Frequency of drug addicts eat 3x / day with white rice consumed every day. For side dishes consumed 1-5x / week. Consumption of vegetables 1-5x / week. Unlike the long beans were consumed ≤2x / month. Fruits like banana, papaya, watermelon and cucumber consumed with 1-5x frequency / week. Energy consumption drug addicts mostly in the medium category (54.5%). Consumption of protein drug addicts mostly in the category of either 94.4%). Nutritional status of drug addicts in the vast majority is in the normal category (83.1%). Based on these results it is suggested to head the kitchen PSPP Insyaf more unwelcome attention of food or foods that cause allergies that are not often included in the diet or by replacing it with other foods. The energy consumption should be increased in order to meet the needs of drug addicts should be. There needs to be a nutritionist to set up the necessary nutritional needs of drug addicts. Keywords: Food Consumption, Nutritional Status, Drug Addicts